2020
DOI: 10.1002/tox.22995
|View full text |Cite
|
Sign up to set email alerts
|

Nano nickel oxide promotes epithelial‐mesenchymal transition through transforming growth factor β1/smads signaling pathway in A549 cells

Abstract: Our previous study demonstrated that nano nickel oxide (NiO) induce pulmonary fibrosis in rats and collagen excessive formation in A549 cells, which mechanism was related with the increasing transforming growth factor β1 (TGF‐β1) secretion. However, it remains unclear understanding the role of TGF‐β1 in collagen excessive formation. Here, we found nano NiO could directly promote epithelial‐mesenchymal transition (EMT) via the TGF‐β1/Smads pathway in A549 cells. First, cytotoxicity induced by nano NiO has a dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…TGF-β1 activates Smads through the transmembrane receptor serine/threonine kinase, thereby continuously regulating the transcription of target genes ( 110 ), The TGF-β1/Smad signaling pathway functions in IPF mainly through the following three processes: Myofibroblast differentiation, EMT/EndMT and fibrogenesis ( 111 ). TGF-β1 activates PI3K and protein kinase B (PKB)/AKT through a SEMA 7A-dependent mechanism, thereby inducing the formation of EMT and ECM in lung epithelial cells ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 activates Smads through the transmembrane receptor serine/threonine kinase, thereby continuously regulating the transcription of target genes ( 110 ), The TGF-β1/Smad signaling pathway functions in IPF mainly through the following three processes: Myofibroblast differentiation, EMT/EndMT and fibrogenesis ( 111 ). TGF-β1 activates PI3K and protein kinase B (PKB)/AKT through a SEMA 7A-dependent mechanism, thereby inducing the formation of EMT and ECM in lung epithelial cells ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under pathological conditions, the p-Smad2/Smad2 ratio and p-Smad3/Smad3 ratio are increased. Chang et al (37) showed that following exposure to 100 µg/ml nano NiO, the phosphorylation levels of Smad2 and Smad3 genes and proteins in A549 cells both increased, suggesting that NiO leads to abnormal changes in Smad2 and Smad3. Consistent with previous studies, silica increased the expression of TGF-β1, TGF-βRI, TGF-βII, p-Smad2/Smad2 and p-Smad3/Smad3, and decreased Smad7 levels in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It was supported by stronger expression of type 1 collagen, TGF-1, p-Smad2, p-Smad3, -actin, vimentin, E-cadherin and fibronectine, that is, changes that characterized fibrosis development at tissue level. SB431542 substance being an antagonist to TGF-1 was able to block these changes [27]. When A549 cells were exposed to NiO NPs (20 nm in diameter), there was a growth in expression of hemoxigenase-1 (HO-1) and surfactant protein-D, that is, genes regulated by hypoxia-induced transcription factor HIF-1 [28].…”
Section: Cytotoxicity Of Ni-containing Nanomaterialsmentioning
confidence: 99%